Influences of geometrical parameters on the heat transfer characteristics through symmetry trapezoidal-corrugated channel using SiO2-water nanofluid - K. Ajeel, Raheem; W. Salim, W.S.-I; Hasnan, Khalid (Elsevier, 2019)
Enhancing the geometrical parameters design of thermal devices leads to promote the thermal performance and boost design plan of these devices and make it more compact. In the current study, heat transfer and flow characteristics of the symmetry trapezoidal-corrugated channel with silicon dioxide (SiO2) - water as nanofluid was performed numerically over Reynolds number ranges of 10,000–30,000. The influence of geometrical parameters including height-to-width ratio (h/W) and pitch-to-length ratio (p/L) on the thermal and hydraulic characteristics are evaluated. A numerical simulation covers nanofluid with SiO2 volume fractions 8% and carried out by employing the finite volume method (FVM) and SIMPLE algorithm for discretization of the governing equations and coupling of the pressure-velocity system while the k−ε turbulence model was employed to compute the turbulent flow. The outcomes revealed that the (h/W) ratio has a more influence on the promotion of heat transfer compared with the (p/L) ratio. At Reynolds number 30000, there is 16.63% increment in Nuav due to a decrease of the (p/L) ratio from 0.175 to 0.075, while the increment about 99.45% due to an increase of the (h/W) ratio from 0.0 to 0.05. The numerical results indicate that the h/W of 0.05 with a p/L of 0.075 are the optimum parameters and have shown significant improvement in thermal performance factor. Furthermore, new correlations for Nusselt number and friction factor are developed and reported.